Microstructure and wear behavior of a Cr-Mo-Nb alloyed manganese steel - Ayadi, Souad; Hadji, Ali; Hakan, Kaleli; Selman, Demirtas (ELSEVIER, 2020)
In this study, microstructure and wear behavior of chromium, molybdenum and niobium alloyed manganese steel were examined and compared to manganese steel containing a low chromium content. Two heat treatments were applied one at 1050 degrees C and the other at 1100 degrees C followed by water quenching. The microstructures were characterized by optical microscopy and scanning electron microscopy (SEM) equipped with an energy dispersive spectrometer (EDS). Rockwell C hardness (HRC) and Vickers microhardness were also measured. Wear behavior in dry conditions was investigated under a load of 300 N using pin-on-disc method. Tribological behavior in boundary lubricated conditions under a load of 60 N at high temperature (100 degrees C) was studied using a custom-made reciprocating tribometer by measuring the mass loss and the friction coefficient. 5W-40 engine oil was used as lubricant. AFM analysis and roughness 2D and 3D of the tested samples were measured. The results show that the as-cast microstructure of the studied manganese steels consists of an austenitic matrix and secondary carbides. Heat treatments at high temperatures change the microstructure and favors the formation of martensite and retained austenite. The increase of heat treatment temperature and addition of Cr, Mo and Nb increase the rate of the formed martensite, which improves the hardness, the wear resistance and the tribological behavior. 5W-40 engine oil favors the formation of tribofilm under the mechanical action during the test, which decreases the friction coefficient of heat treated chromium, molybdenum and niobium alloyed manganese steel. In addition, this oil promotes a polishing wear of the same steel heat treated at 1100 degrees C and colored martensite in blue. (C) 2020 The Author(s). Published by Elsevier B.V.
Keywords: Alloyed manganese steel; Heat treatment; Microstructure; Hardness; Wear; Friction coefficient; Materials Science; Metallurgy & Metallurgical Engineering